Approach and management considerations in low phospholipid associated cholelithiasis (LPAC) syndrome - Suresh, Indrajit; E., Lokesh; Nanaiah, Amrit; Nanaiah, Soumya Ganesh; C., Suhas; D., Chandrababu (International Journal of Research in Medical Sciences, 2018)
Low phospholipid associated cholelithiasis (LPAC) syndrome, first described in 2001, could be the causality in a significant number of young patients with cholelithiasis, who have a recurrence of symptoms despite cholecystectomy. A mutation of the ABCB4/MDR3 gene, causes a disruption in the translocation of phosphatidylcholine, resulting in bile acid mediated biliary tract injury. The ABCB4 gene is also implicated in other diseases such as progressive familial intrahepatic cholestasis type 3, which is greater in severity and tools like genotyping can aid the physician in prognostication, as well as determining the response to medical therapy. A few symptomatic patients develop features of biliary obstruction due to intrahepatic calculi, and they require interventions-which may be endoscopic or surgical in nature. Although a majority of patients with LPAC syndrome respond well to ursodeoxycholic acid (UDCA) therapy, close monitoring is warranted to keep a check on disease progression.